Impact of floor plans on visibility among healthcare members in inpatient care units: Employing agent-based simulation and social network analysis - Hao Yuan; Ying Zhou (Frontiers of Architectural Research)
Healthcare collaboration is crucial for reducing medical errors and ensuring patient safety, and effective collaboration is closely linked to visibility. However, research on how floor plans affect visibility among healthcare members (VHM) in inpatient care units is still insufficient, complicating architectural design decisions. This stems from the lack of methods to assess VHM in inpatient care units, where healthcare members' movements continuously alter their relative positions and visual relationships.This study proposes a novel method integrating agent-based simulation and social network analysis to assess VHM. The method first collects behavioral data from healthcare members to execute agent-based simulation. Subsequently, the simulated positions of healthcare members are used to construct visibility networks. Finally, social network analysis is applied to evaluate the VHM.The findings indicate: (1) the “multi-ring + branching” corridor shape exhibits the highest visibility; (2) shared staff stations improve visibility across different healthcare professionals; (3) spatial relationships between nurse stations and assigned patient rooms affect visibility disparities; (4) mobile nursing stations and interconnected support areas enhance visual communication across disparate zones.This research provides the first quantitative analysis of floor plan effects on VHM. The proposed method offers broad applicability for enhancing visibility assessment, improving healthcare collaboration and reducing medical errors.